2019
DOI: 10.1002/wer.1040
|View full text |Cite
|
Sign up to set email alerts
|

Origin and formation mechanism of salty water in Zuli River catchment of the Yellow River

Abstract: The Zuli River is one of the branches of the upper Yellow River, as an inland catchment with semiarid climate in northwestern China, and the formation, evolution, and development of brackish water at such a large scale have remained unclear. This study aims to find clues about the origin and formation mechanism of salty water through multiple methods of hydrochemistry and isotope hydrology. The results show that groundwater is dominantly recharged by precipitation, and the river water was mainly recharged by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 45 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…The Boron isotope ratios of the river water samples displayed a broader range (17.45 (Table 1) The strata of the mountain area in the headwater of the Zuli River are mainly composed of a set of marine carbonate rocks (Zhan et al, 2010). In our previous study, groundwater was considered as recharged by precipitation in the headwaters based on the analysis of stable isotopes data (δ 2 H, δ 18 O) (Liu et al, 2019). The groundwater in the headwater region is characterized by higher strontium concentration and 87 Sr/ 86 Sr ratios relative to those determined for precipitation (strontium concentrations: (0.002-0.3mg/l), 87 Sr/ 86 Sr ratio:0.7078-0.7092 (Bullen et al, 1996))( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Boron isotope ratios of the river water samples displayed a broader range (17.45 (Table 1) The strata of the mountain area in the headwater of the Zuli River are mainly composed of a set of marine carbonate rocks (Zhan et al, 2010). In our previous study, groundwater was considered as recharged by precipitation in the headwaters based on the analysis of stable isotopes data (δ 2 H, δ 18 O) (Liu et al, 2019). The groundwater in the headwater region is characterized by higher strontium concentration and 87 Sr/ 86 Sr ratios relative to those determined for precipitation (strontium concentrations: (0.002-0.3mg/l), 87 Sr/ 86 Sr ratio:0.7078-0.7092 (Bullen et al, 1996))( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Current knowledge typically attributes the salinization of groundwater in most inland areas to the mixing of old groundwater in deep strata (Herrera et al, 2018), which usually means the salinity of groundwater originated from long periods of water-rock interactions (Petrides, Cartwright, & R.Weaver, 2006;Skrzypek, Dogramaci, & F.Grierson, 2013). However, our recent study showed that even under the rapid renewal of groundwater, the fresh groundwater from the headwaters still evolves into brackish water with rapid salinization (Liu et al, 2019). Several hypotheses have been advanced in previous studies as to the source of salinity in brackish water.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations